Analysis Of Endorser Credibility And Content Marketing On Consumer Attitudes Towards Sukabumifoodies Advertisements (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study was to determine the description of Endorser Credibility and content marketing on Consumer Attitudes on Instagram Sukabumifoodies. To determine the effect of Source / Endorser Credibility on Consumer Attitudes on student followers of Sukabumifoodies Instagram. To determine the role of content marketing on consumer attitudes on the Sukabumifoodies Instagram. The object of this research is about Source / Endorser Credibility, Content Marketing and Consumer Attitudes towards advertising. The research method used by researchers is quantitative research with a descriptive clausal approach. The population in the research conducted by researchers was Sukabumifoodies Instagram followers with a sample of 398 respondents. Data collection used in this study includes primary data and secondary data, namely observation, questionnaires or questionnaires, literature study and documentation. The results of this study are that there is a positive and significant influence between the credibility of the Source / Endorser on consumer attitudes and content marketing has a significant positive relationship with consumer attitudes because Sukabumifoodies promotes its products through marketing content.
Keywords: Endorser Credibility, Content Marketing, Consumer Attitudes, Sukabumifoodies Advertising